UJI AKTIVITAS ANTIDIABETES EKSTRAK ETANOL DAUN SENDOK (Plantago major L.) PADA TIKUS PUTIH JANTAN YANG DIINDUKSI ALOKSAN - Supartiningsih Supartiningsih; Jon Kenedy Marpaung; Adiansyah Adiansyah; Hapsah Junita Siregar (UNIVERSITAS SARI MUTIARA INDONESIA, 2018)
Spoon leaves contain active ingredients, namely tannins, flavonoids, sterols, and polysaccharides. These compounds may be responsible for providing a hypoglycemic effect. This study aims to determine the characterization of the ethanol extract of spoon leaves in male white rats induced by alloxan. Diabetic rats were grouped into five treatment groups, each group consisted of 5 rats. Group I (CMC-Na suspension 0.5% w/v), group II (glibenclamide 0.45 mg/kg BW); Groups II, III, and IV (EEDS doses of 200 mg/kg BW, 400 mg/kg BW, and 600 mg/kg BW) were taken orally for 15 consecutive days. Furthermore, the measurement of glucose levels was observed and measured with a glucometer on days 3, 5, 7, 9, 11, 13, and day 15. The results of the examination of simplicia characteristics showed that the water-soluble extract content was 13.47%, the ethanol-soluble extract content was 12.84%, the total ash content was 3.29%, and the acid insoluble ash content was 0.29%. The results of the analysis of the administration of EEDS showed a significant effect of reducing blood glucose levels in mice compared to the 1% CMC-Na control group. The best decrease in blood glucose levels on the 15th day was shown in the 600 mg/kg BW dose group. Statistical test results (a = 0.05) showed that EEDS at a dose of 400 mg/kg BW and a dose of 600 mg/kg BW were not significantly different from glibenclamide at a dose of 0.45 mg/kg BW.